Cinco de Mayo - Rissman, Rebecca (Chicago : Heinemann Library, 2011)
An introduction to Cinco de Mayo that discusses when and why the holiday is celebrated, the traditions associated with it, and its related symbols.
What is a holiday? -- The story of Cinco de Mayo -- Celebrating cinco de Mayo -- Cinco de Mayo symbols -- Calendar.
Includes index.
1.9
K-3.
K-3
Keywords: Cinco de Mayo (Mexican holiday) -- Juvenile literature; Puebla, Battle of, Puebla de Zaragoza, Mexico, 1862 -- Juvenile literature; Cinco de Mayo (Mexican holiday); Puebla, Battle of, Puebla de Zaragoza, Mexico, 1862.; Cinco de Mayo (Holiday); Puebla, Battle of, Puebla de Zaragoza, Mexico, 1862.; Readers (Elementary).